The Middle to Later Stone Age transition at Panga ya Saidi, in the tropical coastal forest of eastern Africa. Issue 153 (April 2021) - Shipton, Ceri; Blinkhorn, James; Archer, Will; Kourampas, Nikolaos; Roberts, Patrick; Prendergast, Mary E.; Curtis, Richard; Herries, Andy I.R.; Ndiema, Emmanuel; Boivin, Nicole; Petraglia, Michael D.
Abstract: The Middle to Later Stone Age transition is a critical period of human behavioral change that has been variously argued to pertain to the emergence of modern cognition, substantial population growth, and major dispersals of Homo sapiens within and beyond Africa. However, there is little consensus about when the transition occurred, the geographic patterning of its emergence, or even how it is manifested in the stone tool technology that is used to define it. Here, we examine a long sequence of lithic technological change at the cave site of Panga ya Saidi, Kenya, that spans the Middle and Later Stone Age and includes human occupations in each of the last five Marine Isotope Stages. In addition to the stone artifact technology, Panga ya Saidi preserves osseous and shell artifacts, enabling broader considerations of the covariation between different spheres of material culture. Several environmental proxies contextualize the artifactual record of human behavior at Panga ya Saidi. We compare technological change between the Middle and Later Stone Age with on-site paleoenvironmental manifestations of wider climatic fluctuations in the Late Pleistocene. The principal distinguishing feature of Middle from Later Stone Age technology at Panga ya Saidi is the preference for fine-grained stone, coupled with the creation of small flakes (miniaturization). Our review of the Middle to Later Stone Age transition elsewhere in eastern Africa and across the continent suggests that this broader distinction between the two periods is in fact widespread. We suggest that the Later Stone Age represents new short use-life and multicomponent ways of using stone tools, in which edge sharpness was prioritized over durability.